CONVERSION BANK EFFECT: QONUN ACEH DAN KESEJAHTERAAN - Muhammad Abdul Rohman (I-Finance Journal, 2019)
Two phenomena that occurred in Aceh Province after the tsunami disaster, the first phenomenon was a slowdown in poverty reduction in Aceh Province in rural and urban areas and an increase in total assets, financing, third party funds, Islamic banks' people's financing under the pretext of the existence of Aceh Qonun containing conversion Aceh banks from conventional to Islamic. This research tries to relate the two phenomena, how is the influence of the Aceh qonun on the formation of Islamic banks on welfare. This type of research is quasi-experiment with the difference in difference method to analyze the data. The results of this study indicate that someone who has a bank account will tend to increase one's welfare than someone who does not have a bank account. then a person living in Aceh who experienced the treatment of the enactment of Qanun in Aceh actually tends to be less Prosperous than someone who lives outside Aceh. While the combination of financial access and the existence of Aceh qonun will have an impact on people's welfare. The policy implication of this research is the existence of Sharia Qanun which regulates finance in Aceh is not enough to make an increase in welfare, so it needs to be combined with a financial inclusion program in order to bring about an increase in the quality of people's lives.